Elemental re-distribution inside shear bands revealed by correlative atom-probe tomography and electron microscopy in a deformed metallic glass. (15th July 2019) - Balachandran, Shanoob; Orava, Jiri; Köhler, Mathias; Breen, Andrew J.; Kaban, Ivan; Raabe, Dierk; Herbig, Michael
Abstract: A density variation in shear bands visible by electron microscopy is correlated with compositionally altered locations measured by atom-probe tomography in plastically-deformed Al85.6 Y7.5 Fe5.8 metallic-glass ribbons. Two compositionally distinct regions are identified along shear bands, one is Al-rich (~92 at.%), the other is Al-depleted (~82.5 at.%) and both regions show marginal concentration fluctuations of Y and Fe. The elemental re-distribution is observed within shear bands only, and no chemical exchange with the surrounding glassy matrix is observed. Graphical abstract: Unlabelled Image